Menerapkan Etika Ibn Miskawaih dalam Pembelajaran Pendidikan Agama Islam - Dwinugroho, Achmad Wahyu; Rofiq, Ahmad Ainur; Sidik, Ahmad Khairudin; Maryono; Cahyono, Yohanes Dwi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Ethics and morals hold significant importance in Islam, representing a fundamental aspect of the Prophet's mission. Among the scholars who extensively explored ethical principles was Ibn Miskawaih, renowned for his expertise in philosophy and history. This article aims to elucidate the ethical concepts propagated by Ibn Miskawaih. The methodology employed involves a thorough literature review drawing from various scholarly sources, including books, journals, and scientific papers. The findings of this research are as follows: Ibn Miskawaih's exploration of the human soul was influenced by notable thinkers such as Plato, Aristotle, and Alfarabi. These influences underscored the belief that happiness can be attained despite the soul's connection to the body, emphasizing the importance of mental actions alongside physical ones. Ibn Miskawaih delineates three levels of the human soul: An Nafs al-bahimiyah, An Nafs as-sabu'iyah, and An Nafs an-nathiqah, each representing distinct stages of spiritual development. The characteristics attributed to the human soul encompass wisdom, courage, temperance, justice, love, and friendship, reflecting the virtues advocated by Ibn Miskawaih. Practical implementation in learning involves the dissemination of beneficial advice, setting a good example (Uswatun Hasanah), and employing a system of rewards and punishments to reinforce ethical conduct. Through this study, we gain insights into the enduring relevance of Ibn Miskawaih's ethical teachings and their potential applications in contemporary Islamic education.